(untitled) (Global Journal of Management and Business Research, 2023)
Abstract- The purpose of this paper is to open a window to a perspective of CSR, in which, due to CSR a win-win situation is created and to simultaneously disprove some misconceptions or false perspectives regarding CSR. In this paper, to support the perspective, examples of some interviewed companies are taken as case studies and a survey is executed to make some points. This paper provides examples and information regarding the benefits of CSR in a more broader and commercial/economic manner as well as philanthropic and ethical manner at the same time, hence disproving false perspectives towards CSR.